Komitmen Organisasi Sebagai Variabel Intervening Lingkungan Kerja terhadap Kinerja Pegawai UPTD Puskesmas Abang II: Penelitian - Anak Agung Ngurah Bagus Danendra (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to analyze Organizational Commitment as an Intervening Variable of Work Environment on Employee Performance at the Abang II Community Health Center UPTD. The population in this study was all 64 employees of the Abang II Community Health Center UPTD. The sampling technique used was a census or saturated sample. The research analysis technique used validity tests, reliability tests, classical assumption tests, and Parth analysis. The results of the analysis indicate that 1) Work environment has a positive effect on organizational commitment; 2) Work environment has a positive effect on employee performance; 3) Organizational commitment has a positive effect on employee performance; 4) Organizational commitment has not been able to act as an intervening variable in the influence of the work environment on employee performance at the Abang II Community Health Center Technical Implementation Unit (UPTD). This study recommends that the Head of the Abang II Community Health Center Technical Implementation Unit (UPTD) improve the work environment by enhancing the work atmosphere, improving employee competency by enhancing self-concept, enhancing employee organizational commitment by increasing employee attendance, and improving employee performance by improving employee work quality.